Archive fever and the genesis of secrecy in Salman Rushdie. Issue 1 (2nd January 2016) - Mishra, Vijay
Abstract : This paper examines the Salman Rushdie papers deposited in the Robert W Woodruff Library [Manuscript, Archives and Rare Books Library] of Emory University. Although at first glance this is by and large an old fashioned archive (of 215 boxes and 55 oversized papers), it is also a digital archive in the sense that much of the author's drafts, letters and sundry material are preserved in computers. The archive has managed to preserve the hard disks in their original form by simulating and incorporating these disks into a PC. The paper examines how the Rushdie archive has been catalogued and what a researcher trained in research methods and textual criticism may do with the archive. Its theoretical template comes from Derrida's short monograph Archive Fever as it reads the Rushdie archive as a repository as well as a 'consignment' which exists within certain laws and power structures. To explore an archive's concealed or repressed items, the paper carefully traces Rushdie's interest in the Islamic genesis of secrecy with reference to the available holograph notes and related material on the 'satanic verses' in the archive.